Antioxidant properties, mineral content and sensory acceptance of napier grass teas as affected by different processing methods - Ng Khai Shin (Universiti Malaysia Terengganu, 2022)
Investigation on the configuration of a towline model incorporated with ship towing system performance is obviously necessary to attain navigational towing safety at sea. Instead of employing typical towing models such as single and symmetrical bridle towline models, an asymmetrical bridle towline configuration is then proposed to improve the ship towing performance during operation. This thesis presents Computational Fluid Dynamics (CFD) analysis on the asymmetrical bridle towline model with respect to its effect on course stability and seakeeping performance of the ship towing system in calm water and waves, respectively. Several towing parameters such as various towing angles, towing speeds and towline lengths have been taken into accounts in the simulation. Here, the course stability performance of the towed barge has been analysed in three degrees-of-freedom i.e., surge sway and yaw motions. Meanwhile, the seakeeping characteristic has been assessed at various wavelengths and wave directions involving five degrees-of-freedom i.e., surge, sway, yaw, heave and pitch motions.